Application of Smart Technology in Marketing Strategy Development: An Overview of the Hotel Industry in Bali - Seno Hadi Saputro; Arninda Arninda; Ferdy Firmansyah; Munawir Munawir (International Journal of Management Science and Information Technology, 2023)
This study aims to analyze the impact of smart technology implementation in the hospitality industry, focusing on issues of privacy and data security, economic and social impact of engagement. of human resources and the importance of transparency and accountability in smart technology design. The research methods used are inductive and qualitative methods with in-depth interpretation. Data is drawn from a variety of scholarly sources and up-to-date information from platforms such as SINTA, Science Direct, Google Scholar, Scopus, and Web of Science. Research results show that the application of smart technology in the hotel industry has a significant impact on many aspects. The first finding highlights the need to prioritize data security and privacy issues. The implications of replacing workers with smart technology have an impact on the local economy and employment structure. Furthermore, this study highlights the need for transparency and accountability in the design of smart technologies, so that customers have clear information and control over their personal data. This finding is consistent with previous research that has identified the risks and social impacts of smart technology adoption in the hospitality industry. Therefore, businesses in the hospitality industry need to develop policies and strategic measures to address negative impacts and ensure the ethical and responsible adoption of smart technology. This study provides insight into the impact of smart technology implementation in the hospitality industry and provides a basis for developing sustainable and ethical strategies for smart technology adoption in hospitality.